تأثير خلائط مختلفة من بذور الأعشاب وسماكة وسط الزراعة في إنتاج اللفائف الخضراء (Big rolls) - شيحا هالة (Latakia University Journal -Biological Sciences Series, 2017)
هدف هذا البحث إلى تحديد خلطة الأعشاب الأنسب و سماكة وسط الزراعة الأفضل لإنتاج اللفائف الخضراء و بأقل التكاليف الممكنة, حيث تم اختبار ثلاث خلطات من بذور الأعشاب(SH, TG, SG) و ثلاث سماكات مختلفة (3, 5 و 7 سم). أظهرت النتائج تأثير خلطة بذور الأعشاب في كل من نسبة الإنبات (68,2 – 77,2%) و درجة التغطية (77 – 93%), حيث كانت الخلطة SGهي الأفضل. كما بينت النتائج أن خفض سماكة وسط الزراعة من 7 إلى 3سم اختصر المدة اللازمة للحصول على لفائف جاهزة للتسويق بمعدل 11 إلى 14 يوماً. في حين حسنت زيادة سماكة وسط الزراعة بعض الخصائص النوعية للفائف الخضراء, كدرجة التغطية و درجة اللون, و لكنها عملت في الوقت نفسه على زيادة وزن اللفائف بشكل ملحوظ. حيث وصلت في سماكة 7سم إلى 64,51 كغ\م2 في الخلطةSG مقابل26,17كغ\م2 بسماكة 3سم للخلطة SH وزيادة الوزن صفة غير مرغوبة لأنها تساهم في زيادة نفقات الإنتاج (تكلفة إعداد الوسط, تكاليف عمليات الخدمة, و تكاليف التحميل و النقل) مما قلل معامل الربحية. حققت خلطة الأعشابSHعلى وسط بسماكة 3سمربحاً اقتصادياً أعلى مقارنةً بالمعاملات الأخرى حيث كان معامل الربحية (119,3 %). The aim of this research was to determine the best seed mixture and the preferred thickness of culture medium for big rolls production. Three different seed mixtures(SH, TG, SG)using three thicknesses (3, 5 and 7cm) were experimented. The results showed that the effect of seed mixture was clearly on germination percentage (68.2 – 77.2%) and the rate of coverage (77 – 93%), and the SG seed mixture has given the best results. The decrease of the thickness of medium from 7 to 3cm has reduced the period of ready big rolls production (11 -14 days). The increase of the thickness has improved the quality of big rolls like the coverage rate and the degree of colour. But at the same time it increased the weight significantly (64,51kg/m2for SG seed mixture of 7cm thickness and 26,17kg/m2for SH seed mixture of 3cm thickness). Nevertheless, the increase of the weight also contributed to increase the production costs (medium set up price, agricultural service operations, and the costs of loading and transportation) which reflected negatively on the coefficient of profitability. The SH seed mixture, and the thickness of 3cm has achieved the highest economic profit compared with other treatment. The coefficient of its profitability has reached (119.3%).